PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB DENGAN PENDEKATAN ETNOMATEMATIKA PADA MATERI BANGUN RUANG SISI DATAR - Maryanti, Indra; Suwardi, Tria Ermayani (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2024)
Technology has rapidly developed across various fields, including education, which has been significantly impacted by technological advancements. The development of computer technology can be utilized to assist in creating effective learning media. This research aims to develop web-based interactive learning media using an ethnomathematics approach for teaching flat-sided space shapes to eighth-grade junior high school students. The development model employed in this study is the 4-D or 4-P model, which was modified into three stages: the definition stage (define), the design stage (design), and the development stage (develop). The research subjects consisted of 15 students from SMP Swasta Budi Agung Medan. The instruments used in this research included expert material assessment questionnaires, expert media assessment questionnaires, and student response questionnaires. The findings revealed that the developed web-based interactive learning media with an ethnomathematics approach received a score of 93% from expert media validators, indicating that the media is highly valid. Expert material validators gave a score of 87%, classifying it as very good or highly valid. Meanwhile, the student response assessment showed an average score of 86%, indicating that the media was highly engaging and met the required criteria.